Alterations in the neural circuitry for emotion and attention associated with posttraumatic stress symptomatology - Hayes, Jasmeet Pannu (2009)
Information processing models of posttraumatic stress disorder (PTSD) suggest that PTSD is characterized by preferential allocation of attentional resources to potentially threatening stimuli. However, few studies have examined the neural pattern underlying attention and emotion in association with PTSD symptomatology. In the present study, combat veterans with PTSD symptomatology engaged in an emotional oddball task while undergoing functional magnetic resonance imaging (fMRI). Veterans were classified into a high or low symptomatology group based on their scores on the Davidson Trauma Scale (DTS). Participants discriminated infrequent target stimuli (circles) from frequent standards (squares) while emotional and neutral distractors were presented infrequently and irregularly. Results revealed that participants with greater PTSD symptomatology showed enhanced neural activity in ventral-limbic and dorsal regions for emotional stimuli and attenuated activity in dorsolateral prefrontal and parietal regions for attention targets. In the anterior cingulate gyrus, participants with fewer PTSD symptoms showed equivalent responses to attentional and emotional stimuli while the high symptom group showed greater activation for negative emotional stimuli. Taken together, the results suggest that hyperresponsive ventral-limbic activity coupled with altered dorsal-attention and anterior cingulate function may be a neural marker of attention bias in PTSD.